Novel optical applications inspired by the Morpho butterfly's coloration: technology transfer from reflection to transmission. (1st June 2022) - Saito, Akira; Yamashita, Kazuma; Hattori, Takuma; Kuwahara, Yuji
Abstract: Morpho butterfly's blue is a famous example of structural colors but its mechanisms are exceptional, accompanied by a mystery. This color is created by interference from an ordered nanostructure, whereas the single color in wide angles contradicts the interference. This secret is attributed to a specific nanostructure having both order and disorder. After proof of this mechanism by artificial reproduction, we have found its wide potential applicability, and developed the fabrication technology in several directions. Moreover, by converting this reflective principle to transmission, we have also found a possibility of new optical transmission devices with high transmittance, wide angular spread, low color dispersion, compactness, and controllability of light spread which have been impossible to meet simultaneously. Although our originally proposed nanostructure was difficult to fabricate, we have designed a feasible nanostructure to solve the problem. Finally, a Morpho -type window was successfully fabricated and verified, which can serve as a novel optical diffuser.